The influence of big data analytic capabilities building and education on business model innovation - Cui, Yong; Firdousi, Saba Fazal; Afzal, Ayesha; Awais, Minahil; Akram, Zubair (Frontiers in Psychology, 2022)
As organizations are benefiting from investments in big data analytics capabilities building and education, our study has analyzed the impact of big data analytics capabilities building and education on business model innovation. It has also assessed technological orientation and employee creativity as mediating and moderating variables. Questionnaire data from 499 managers at enterprises in Jiangsu, China have been analyzed using Structural Equation Modeling (SEM) in SmartPLS. Big data analytics capabilities building and education strengthen technological orientation and increase business model innovation. Technology orientation increases business model innovation and plays a mediating role. Employee creativity also boosts innovation. These findings show that business managers should adopt and promote a technological orientation. They should hire and train employees with big data education and training. Organizations can try to select and support employees who show creativity.